2015
DOI: 10.1111/josh.12278
|View full text |Cite
|
Sign up to set email alerts
|

School Gardens Enhance Academic Performance and Dietary Outcomes in Children

Abstract: This small set of studies offers evidence that garden-based learning does not negatively impact academic performance or FV consumption and may favorably impact both. Additional studies with more robust experimental designs and outcome measures are necessary to understand the effects of experiential garden-based learning on children's academic and dietary outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
112
0
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(131 citation statements)
references
References 41 publications
5
112
0
14
Order By: Relevance
“…[9,10]. Increase in access to fruits and vegetables increased in planning and preparing meals at home [11][12][13].…”
Section: Resultsmentioning
confidence: 99%
“…[9,10]. Increase in access to fruits and vegetables increased in planning and preparing meals at home [11][12][13].…”
Section: Resultsmentioning
confidence: 99%
“…Future research should examine how elements of school culture influenced the implementation and adherence to these guidelines. Finally, studies have shown how programs that improve the health of children can have promising results in improving academic outcomes . Collecting additional data on the potential for health promotion programs to improve academic outcomes may promote more widespread adoption and support for school‐based obesity prevention interventions among staff, administrators, and parents.…”
Section: Discussionmentioning
confidence: 99%
“…Dewey (1963) defined this as experiential learning, meaning learning through experience and experiment. In addition, using the school garden as a place for teaching the curriculum can influence children's academic performance positively (Berezowitz, Bontrager Yoder, & Schoeller, 2015).…”
Section: Discussionmentioning
confidence: 99%